Hsa_circ_0037128 aggravates high glucose-induced podocytes injury in diabetic nephropathy through mediating miR-31-5p/KLF9. (19th May 2022) - Fang, Rong; Cao, Xiangchang; Zhu, Yaping; Chen, Qiming
Abstract: Background: Circular RNA is a key regulator involved in the progression of many human diseases including diabetic nephropathy (DN). However, the role and mechanism of hsa_circ_0037128 in the occurrence and development of DN remains to be explored. Methods: High glucose (HG)-induced podocytes were used to construct in vitro DN models. The expression of hsa_circ_0037128, microRNA (miR)-31-5p, and Kruppel-like factor 9 (KLF9) was determined using quantitative real-time polymerase chain reaction. The viability and apoptosis of podocytes was measured using cell counting kit 8 assay and flow cytometry. Western blot analysis was performed to examine the protein levels of apoptosis markers and KLF9 in podocytes. Inflammation factors were detected by ELISA assay, and oxidative stress markers were assessed by corresponding Assay Kits. In addition, the interaction between miR-31-5p and hsa_circ_0037128 or KLF9 was verified using dual-luciferase reporter assay and RIP assay. Results: Our data suggested that hsa_circ_0037128 was highly expressed in DN patients and HG-induced podocytes. In HG-induced podocytes, hsa_circ_0037128 knockdown could alleviate HG-induced podocytes injury. In the term of mechanism, hsa_circ_0037128 could sponge miR-31-5p to upregulate KLF9. MiR-31-5p inhibitor could reverse the negative regulation of hsa_circ_0037128 silencing on HG-induced podocytes injury. Also, miR-31-5p relieved HG-induced podocytes injury, and this effect also could be reversed by KLF9 overexpression. Conclusion: In summary, our data showed that hsa_circ_0037128 could promote HG-induced podocytes injury via regulating miR-31-5p/KLF9 axis, showing that hsa_circ_0037128 might be a target for DN treatment.